THE FEATURES OF GEOLOGICAL STRUCTURE OF UPPER CRUST OF SOUTH-EAST UKRAINIAN SHIELD - PIHULEVSKYI, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article describes some aspects of the geological structure of the upper crust and Middlednieper and Priazovsky megablockes of south-easten part of the Ukranian Shield at section – 5 km. Areal development of various complexes of rocks and formations is presented. The conclusion about displacements at the depth of the major faults of Ukrainian Shield is made. The results obtained allow a new way to consider the prospects of searches of various types of minerals.